The Impact of Paternalistic Leadership as a Mediating Factor in BUMN on Organizational Commitment with an Ethical Climate - Laksana, Bayu; Handina Pamungkas, Alfito; Lubna Akbar, Bobby; Rudiantono, Yodi (International Journal of Business, Law, and Education, 2024)
The purpose of this study is to examine how Paternalistic mediating Organizational Commitment with an ethical climate. Quantitative approaches are employed in this study. using methods for gathering data such as interviews and questionnaires. The study included 180 workers from BUMN as respondents. Path analysis is the analytical technique employed. The research's analysis's findings demonstrate that paternalistic leadership significantly enhances organizational commitment and the ethical atmosphere.